Retreatment and prolonged therapy with subcutaneous bortezomib in patients with relapsed multiple myeloma: A randomized, controlled, phase III study. (30th October 2017) - Terpos, Evangelos; Gobbi, Marco; Potamianou, Anna; Lahaye, Marjolein; Couturier, Catherine; Cavo, Michele
Abstract: Objectives: This randomized, international, multicenter, open‐label phase III study investigated the effects of experimental retreatment with subcutaneous bortezomib plus dexamethasone (VD) followed by prolonged bortezomib therapy vs standard VD retreatment in patients with relapsed/refractory multiple myeloma. Methods: Patients were randomized (2:1) to receive either experimental (n = 53) or standard (n = 27) retreatment, stratified by the number of prior therapy lines. Results: The study was terminated prematurely with insufficient enrollment to adequately compare the retreatment therapies; results should be considered descriptive. After a median follow‐up of 21.2 and 20.0 months in the experimental and standard arms, respectively, the median progression‐free survival (primary endpoint) was 7.2 months (95% confidence interval 5.7‐9.0) vs 7.8 months (4.9‐11.7). The overall response rate was 66% and 52% for experimental and standard retreatment regimens, respectively. Thrombocytopenia was the most common and most differentially observed grade ≥3 adverse event (experimental: 9% vs standard: 22%). Any‐grade peripheral neuropathies (including peripheral sensory neuropathies) were reported in 23% vs 37% of patients. Conclusions: This study showed no significant benefit with experimental vs standard VD retreatment therapy. Further investigations are required to determine whether the experimental retreatment regimen is a suitable alternative to the current standard retreatment regimen.